Child marriage discourse according to al-Qaradawi’s fiqh methodology - Muhammad Al-Ghazalli Abdol Malek; Mohd Al Adib Samuri; Ramadhita; Vargholy, Muhammad Najih (Penerbit Universiti Kebangsaan Malaysia, 2024)
The polemic on the issue of child marriage has not only been debated among human rights groups in recent decades but has also been included in the discourse of contemporary Muslim scholars. Yusuf al-Qaradawi is a contemporary scholar who is responsive in discussing issues of women and girls that concern the international community, including child marriage. This article explores issue of child marriage from al-Qaradawi’s fiqh methodology, which offers solutions to contemporary societal issues according to the Islamic legal framework. Qualitative methods through a content analysis were used in al-Qaradawi’s work on Islamic law and child marriage. This article shows that al-Qaradawi’s position on the issue of child marriage is centred on the priority of protecting children’s rights from harmful traditional practices based on the Siyasah al-Shar’iyya. The government should adopt al-Qaradawi’s point of view to reforming the Islamic Family Law Enactment to protect the child’s best interest from this harmful practice.